Helicobacter pylori associated with breastfeeding, nutritional status and recurrent abdominal pain in healthy Nigerian children - Senbanjo, Idowu O; Oshikoya, Kazeem A; Njokanma, Olisamedua F (The Journal of Infection in Developing Countries, 2014)
Introduction: There is limited knowledge about the associations of Helicobacter pylori (H. pylori) infections in developing countries. This study aimed to determine the current prevalence and associations of H. pylori infection with breastfeeding practices, nutritional status, and recurrent abdominal pain (RAP) in a group of apparently healthy children and adolescents in Lagos, Nigeria. Methodology: This was a prospective hospital-based study conducted at the Lagos State University Teaching Hospital that involved 118 children who came to the hospital for routine pediatric care. Seroprevalence status of the children was determined by measuring immunoglobulin G antibodies against H. pylori using enzyme-linked immunosorbent assay (ELISA). Results: Seventy-five (63.6%) children were seropositive for H. pylori. The prevalence of H. pylori infection increased significantly from 40.4% in children less than five years of age to 85.1% at six to ten years of age (χ2 = 20.9, p < 0.001). H. pylori infection was associated with low social class (OR = 3.24; 95% CI = 1.20-8.23, p = 0.016) and with RAP (OR = 3.47; 95% CI = 1.55-7.79, p = 0.002), but no association was observed with exclusive breastfeeding, duration of breastfeeding, and under-nutrition. Conclusions: The prevalence of H. pylori infection is high, particularly among children from low socioeconomic backgrounds in Lagos, Nigeria. It is associated with RAP. The effect of this infection on children’s health requires further studies.